(untitled) (Research, Society and Development, 2021)
Quilombola communities are considered vulnerable groups and need actions focused on reality in order to improve the quality of life of this population. The objective of this study is to develop and validate an investigation instrument that allows analyzing the association of the main diseases related to water and COVID-19 in quilombola communities, as well as knowing the socioeconomic and environmental profile of this population group. Stringent content validation methodological evaluation tests were conducted. Initially, the first version of the instrument containing 79 questions was created based on a review of the literature and submitted to evaluation by five experts who have experience in activities developed with quilombolas. After corrections and validation by experts, the second version with 68 questions was applied as a pre-test with 50 individuals. The validity of the final version of the instrument was considered satisfactory and constitutes a useful tool in the investigation of health, socioeconomic and environmental conditions in quilombola communities.